(untitled) (Proceedings OPTIMAL, 2024)
Background: Prayer according to the language "ad-du’aa" means calling, asking for help, or begging for something. While dhikr reviewed etymologically begins with the word "dzakara" which is interpreted as mentioning, purifying, combining, maintaining, understanding, studying, giving and advice. Handling post-CS pain can be done with a pharmacological or non-pharmacological approach. Pharmacologically with analgesic drugs such as nonsteroidal drugs (NSAIDs), (OPIOIDs) morphine, benzodiazepines, ketamine. Non-pharmacological pain management consists of pain treatment based on physical stimulation and cognitive behavior. Research Objective: To determine the effect of prayer and dhikr intervention on reducing Post SC pain at RSU Islam Klaten. Research Method: This study used PreExperiment Design with a one group pre-test and post-test design. The sample used was 50 people. Data processing was carried out using computing, with data processing steps using univariate and bivariate analysis. Research Results: The pain score before the prayer and dhikr intervention in post-SC patients obtained the highest pain level of 8 with an average of 5.36. The pain score after the prayer and dhikr intervention in post-SC patients obtained the highest pain level of 7 with an average of 4.22. the results of the t-test calculation using the paired sample t-test obtained a p value = 0.00 <0.05. Conclusion: Based on the results of the study, it can be concluded that there is an influence of prayer and dhikr to reducing post-SC pain at the Klaten Islamic Hospital.